Hubungan Manusia dengan AI dan Relevansinya dengan Nilai Ketuhanan, Kemanusiaan, dan Keadilan dalam Pancasila: (Studi Kasus Film “Her”) - Haryanto, David; Yehuda, Michael Christian; Reinanda, Muhammad Abdi; Alfredo, Ronald Bryan; Sulu, Verrel Novendra (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2023)
Her is a romantic drama science fiction film that explains how humans in the future are dependent on AI technology. This research aims to analyze the relationship between humans and AI in the film 'Her' based on the Pancasila perspective. Some values from this film can be analyzed based on the precepts of Pancasila, especially the precepts of divinity, humanity, and justice. The research was conducted qualitatively, with literature study as the data acquisition technique. Data was also obtained by observing the movie 'Her'. The results showed that the first principle of Pancasila contains the value of divinity and states that everyone has the right to embrace, adhere to, and worship in accordance with their respective religions. However, the relationship between humans and artificial intelligence (AI) raises questions in the context of religious teachings. The second principle means humanity and at the same time the ethics of the Indonesian people as living beings. This is shown by the nature of the main character who treats AI as human beings without demeaning or discriminating. It can be seen from the other side why the main character's behavior of respecting AI's character can be considered as a way to fight the character's sadness and loneliness. The fifth precept has the meaning of the value of equality and equality where everyone has rights that cannot be revoked by anyone. Rights will never be separated from obligations, for example someone has the right to express an opinion, he also has an obligation to respect the opinions of others and not be discriminatory. It can be concluded that, first, human relations with AI are prohibited in the two major religions in Indonesia because they violate the stipulated provisions. Second, human values are well lived because of the attitude of equality. Third, everyone has freedom or rights that cannot be revoked by anyone, such as the example of the main character in this film, namely the right to love and be loved.